Design and analysis a new spoiler for UMP HEV using CFD - Muhammad Najmudin, Mohd Taib (2007)
This thesis presents the design and develops new rear spoilers to overcome a drag force that is created because of low pressure zone at the rear hack. With the new design of rear spoiler for the Proton iswara Hybrid Electrical Vehicle (BV) UMP, the performance of the car had increased from the aspect of acceleration and also from the aspect of handling of the car, the controlled speed of this research is from 80 km/hr to 110 km/hr. The design of rear spoiler is based on the type of the car used, therefore aerodynamic shape of the body and the point of the rear spoiler is important in this research. In this research 2 spoilers have been choosing that are squareback and fastback rear spoilers. According to that reason, low pressure zone will be annihilated slowly if one of the rear spoilers is put at the rear back of the car. Refer to data testing obtained, using squareback spoiler will reduce more low pressure zone than using fastback spoiler. Based on the analysis, the suitable place to mount the rear spoiler is at the point where squareback spoiler is mounted and it synchronized with the shape of the Proton Iswara HEy. It will give additional information to the performance car researcher to continue on this research thoroughly about the effect of spoiler on any HEY car and eventually to Malaysia's first HEV race car. In the future, this factor will give benefit to the Malaysia car developer especially HEY car developer.